2007
DOI: 10.1029/2005jf000455
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation in the Val Pola rock avalanche, Italian Alps

Abstract: [1] Grain size data from the deposit of the 1987 Val Pola rock avalanche (central Italian Alps) are compared with data concerning rock avalanching, rock fragmentation, and comminution. The Weibull distribution fits a small part of the entire particle-size distribution of debris samples, with a mean value of the curve shape factor of 0.54 ± 0.28. This is typical of multiple comminution, or fragmentation with much shearing. A fractal distribution fits over a greater size range. Computed fractal dimensions range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
181
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(195 citation statements)
references
References 83 publications
(135 reference statements)
14
181
0
Order By: Relevance
“…The evident discrepancy between observed and predicted final grain size shows, unsurprisingly, that only a small fraction of the available energy goes into the comminution process and that the fragmentation in a rock avalanche might be dynamically different from that occurring in a comminution device. Similar conclusions have been drawn by Crosta et al [4] for the recent Valpola landslide in northern Italy. In any case, it is concluded that the energy estimates are not informative on the physics of fragmentation, and one has to consider the kinetics of the fragmentation process.…”
Section: Energy Estimatessupporting
confidence: 76%
See 2 more Smart Citations
“…The evident discrepancy between observed and predicted final grain size shows, unsurprisingly, that only a small fraction of the available energy goes into the comminution process and that the fragmentation in a rock avalanche might be dynamically different from that occurring in a comminution device. Similar conclusions have been drawn by Crosta et al [4] for the recent Valpola landslide in northern Italy. In any case, it is concluded that the energy estimates are not informative on the physics of fragmentation, and one has to consider the kinetics of the fragmentation process.…”
Section: Energy Estimatessupporting
confidence: 76%
“…The expression can also be transformed as the ratio of two incomplete gamma functions. Table 2 shows the results of the calculation compared to data taken from Crosta et al [4]. According to the measurements of ref.…”
Section: Role Of Static Force Chains In the Process Of Fragmentationmentioning
confidence: 93%
See 1 more Smart Citation
“…Most landslide dams are highly heterogeneous along depth and along the run-out direction (Dunning, 2006;Crosta et al, 2007;Chang et al, 2009;Evans at al., 2007), which is a crucial factor in determining the failure time and outflow hydrograph (Costa and Schuster, 1988;Casagli et al, 2003). The capability of existing models to consider the variations in soil erodibility along depth has yet to be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Complete inventories including deposited blocks of all sizes are difficult to obtain. Several researchers mainly working on rock blasts, have used photoanalytical techniques to obtain the fragment size distribution (Crosta et al 2007). However these provide results only for the block area and not for the volume.…”
Section: Introductionmentioning
confidence: 99%